A unified "top-down" approach for the synthesis of diverse lead-like molecular scaffolds. (15th April 2022) - Townley, Chloe; McMurray, Lindsay; Marsden, Stephen P.; Nelson, Adam
Graphical abstract: Abstract: A "top-down" synthetic approach enabled the step-efficient synthesis of 21 diverse novel molecular scaffolds. The scaffolds were derived from four complex intermediates that had been prepared using cycloaddition chemistry. Scaffold-hopping of these intermediates was achieved through attachment of an additional ring, ring cleavage, ring expansion and/or ring fusion. It was shown that the resulting scaffolds could be decorated to yield diverse lead-like screening compounds.